Teaching for transformation: the use of narrative metaphor to develop reflexive professionals - Sliep, Yvonne (Acta Academica: Critical views on society, culture and politics, 2010)
This article emphasises the importance of developing critical reflexivity in professionals. Higher education in South Africa is still shaped by socio-economic and political inequalities. This article suggests that transformative teaching practices can respond to the challenges resulting from such inequalities by making use of narrative metaphor. Narrative metaphor embraces the power of stories in teaching and learning through experience-based, constructivist pedagogy. Transformative teaching and learning connects new knowledge with lived experience, resulting in an on-going construction and reconstruction of personal, professional and contextual narratives. Knowledge is thereby co-constructed and participants become part of actively shaping the context in which they live, study and work.